2018
DOI: 10.1002/chem.201804651
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Crystallographic Characterization of Lu3N@C2n (2n=80–88): Cage Selection by Cluster Size

Abstract: The small Sc N cluster has only been found in such small cages as C (2n=68, 78, 80, 82), whereas the large M N (M=Y, Gd, Tb, Tm) clusters choose those larger cages C (2n=82-88). Herein, concrete experimental evidence is presented to establish the size effect of the internal metallic cluster on selecting the outer cage of endohedral metallofullerenes (EMFs) by using a medium-sized metal, lutetium, which possesses an ionic radius between Sc and Gd. A series of lutetium-containing EMFs have been obtained and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
6
22
0
Order By: Relevance
“…Notably, the fullerene cages for U@C 84 and U@C 86 (I) are not the same IPR isomers found for the previously reported Sm@ D 3 d (19)-C 84 , Sm@ C 2 (13)-C 84 , Eu@ D 3 d (19)-C 84 , Eu@ C 2 (13)-C 84 , Eu@ C 2 (11)-C 84 , Yb@ C 2 (13)-C 84 , Lu 2 @ C 2 v (7)-C 84 , Lu 2 @ D 2 d (23)-C 84 , Sc 2 C 2 @ D 2 d (23)-C 84 , Eu@ C 1 (7)-C 86 , Lu 2 @ C s (8)-C 86 , Lu 2 @ C 2 v (9)-C 86 , Lu 2 C 2 @ C 2 v (9)-C 86 , Sc 2 C 2 @ C 2 v (9)-C 86 , Gd 3 N@ D 3 (19)-C 86 , Tb 3 N@ D 3 (19)-C 86 , and Lu 3 N@ D 3 (19)-C 86 . Analysis of cage connectivity identified U@C 84 as U@ D 2 (21)-C 84 and U@C 86 (I) as U@ C s (15)-C 86 , the same C s (15)-C 86 was only reported for Lu 2 @C s (15)-C 86 previously .…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…Notably, the fullerene cages for U@C 84 and U@C 86 (I) are not the same IPR isomers found for the previously reported Sm@ D 3 d (19)-C 84 , Sm@ C 2 (13)-C 84 , Eu@ D 3 d (19)-C 84 , Eu@ C 2 (13)-C 84 , Eu@ C 2 (11)-C 84 , Yb@ C 2 (13)-C 84 , Lu 2 @ C 2 v (7)-C 84 , Lu 2 @ D 2 d (23)-C 84 , Sc 2 C 2 @ D 2 d (23)-C 84 , Eu@ C 1 (7)-C 86 , Lu 2 @ C s (8)-C 86 , Lu 2 @ C 2 v (9)-C 86 , Lu 2 C 2 @ C 2 v (9)-C 86 , Sc 2 C 2 @ C 2 v (9)-C 86 , Gd 3 N@ D 3 (19)-C 86 , Tb 3 N@ D 3 (19)-C 86 , and Lu 3 N@ D 3 (19)-C 86 . Analysis of cage connectivity identified U@C 84 as U@ D 2 (21)-C 84 and U@C 86 (I) as U@ C s (15)-C 86 , the same C s (15)-C 86 was only reported for Lu 2 @C s (15)-C 86 previously .…”
Section: Resultsmentioning
confidence: 45%
“…Accordingly, the intact fullerene cage is generated by combining one half of the cage with the mirror image of the Notably, the fullerene cages for U@C 84 and U@C 86 (I) are not the same IPR isomers found for the previously reported Sm@D 3d (19)-C 84 , 24 Sm@C 2 (13)-C 84 , 24 Eu@D 3d (19)-C 84 , 25 Eu@C 2 (13)-C 84 , 14 Eu@C 2 (11)-C 84 , 14 Yb@C 2 (13)-C 84 , 26 Lu 2 @C 2v (7)-C 84 , 27 Lu 2 @D 2d (23)-C 84 , 28 Sc 2 C 2 @D 2d (23)-C 84 , 29 Eu@C 1 (7)-C 86 , 14 Lu 2 @C s (8)-C 86 , 27 Lu 2 @C 2v (9)-C 86 , 28 Lu 2 C 2 @C 2v (9)-C 86 , 27 Sc 2 C 2 @C 2v (9)-C 86 , 19 Gd 3 N@D 3 (19)-C 86 , 30 Tb 3 N@D 3 (19)-C 86 , 31 and Lu 3 N@D 3 (19)-C 86 . 32 Analysis of cage connectivity identified U@C 84 as U@D 2 (21)-C 84 and U@C 86 (I) as U@C s (15)-C 86 , the same C s (15)-C 86 was only reported for Lu 2 @C s (15)-C 86 previously. 27 It is important to note that D 2 (21)-C 84 is a totally new chiral cage, for which we observe the two enantiomers (cage 1 and cage 1A), see Figure S4.…”
Section: Resultsmentioning
confidence: 59%
“…Until recently, crystallographic results and DFT calculations confirmed that the M 3 N@C 80–88 (M=Lu, Er) isomers also accommodate a planar M 3 N cluster inside (Figure ). Specifically, the M−N distances of the major M 3 N sites in M 3 N@C 80–88 (M=Lu, Er) isomers increase with cage expansion owing to the strong metal–cage interactions to maintain the planar geometry of the M 3 N unit (Figure ).…”
Section: Nitride Clusterfullerenesmentioning
confidence: 99%
“… The M–N distances of the major M 3 N site as a function of the cage size in (a) Lu 3 N@C 80–88 and (b) Er 3 N@C 80–88 series. (Values for Er 3 N@C 86 were obtained from theory).…”
Section: Nitride Clusterfullerenesmentioning
confidence: 99%
See 1 more Smart Citation